Application of Marxist Economic Thought by the Government of Nepal after 2006 - Neupane, Bhim Prasad (Economic Journal of Development Issues, 2012)
This paper aims to discuss the application of Marxist Economic thought by the government of Nepal after the second popular movement of 2006. The paper is based on documents published by the government, publication from National Planning Commission. The paper finds that most of the policies and programs adopted by Nepal Government after 2006 are influenced by Marxist Economic Thought. Economic Journal of Development Issues Vol. 11 & 12 No. 1-2 (2010) Combined Issue Page: 21-32 Uploaded date: 10 April, 2012